الترويج للدواء بولاية الخرطوم: أهم أهدافه والعوامل التي تؤدي إلى تحقيقها - عبد المحمود, علي محمد أحمد (Gezira Journal of Economic and Social Sciences; مجلد 2 عدد 1 (2011), 2011)
The objective of this paper is to study the promotion of pharmaceutical products in Khartoum State, with special emphasis on the most important objectives and the factors that lead to their achievement. The important role played by promotion staff, in giving correct information on pharmaceutical products, drugs or cosmetics, in addition to their role in creating awareness among users to properly handle these products in a correct and safe manner, to protect drugs from damage , and for drugs to be kept out of reach of children because of the dangers of misuse of  these products are all beyond doubt. Although drugs are of great benefit, patients may be at risk if they use drugs without consulting a doctor, or place them within the reach of children. Yet, there is strong competition among pharmaceutical companies in Sudan, which led to increase spending on promotion. The researcher used an analytical statistical method. The data were obtained through secondary sources including books and scientific literature and professional journals. The primary data were obtained using a questionnaire, from a casual study sample from the different localities of Khartoum State. The results obtained suggest that: The main objective to promote the drug is to increase the sales of the company. There are some factors that affect the achievement of the objectives of promotion: including the quality, price and effectiveness of the drug, the method used in its promotion, and the personal characteristics of delegates, the extent of their scientific knowledge of the drug beside their own personal duties. The study concluded that the most important duties of the promoter is to bring the reaction of doctors and pharmacists about the drug concerned to the attention of the company. The study also found that the economic conditions affect the achievement of the objectives of promotion.                                   In light of these results, a number of recommendations were made including that the drug companies can carry out alone or with the relevant authorities, so that they can deliver medicine to the segments of society at affordable prices, leading companies to increase sales and achieve the main objective of the promotion.